Association Between Vehicle Seat Dynamics and Ride Comfort Criteria - Azizan, Amzar; Padil, Husna (International Journal of Engineering and Technology, 2018)
The upfront prediction of subjective ride comfort involves the investigation of vehicle seat structural dynamics coupled with the human body. It has been numerously stated in prior researches that a limit of less than 100Hz, which is the external vibration’s normal description for human sensitivity, would be the output for basic seat resonance. Based on our findings, there are three particular mode shapes which had been indicated to be less than 80Hz. The seat shapes were fore/aft, twisting and lateral shapes. Despite many have proven that ride comfort requirements are quite subjective in nature, researchers are still in ongoing process of developing human vibration standards. For that purpose, they would always evaluate their seats, which were mostly rigid, to acknowledge and ascertain that their seat production process needs to be carried out from time to time. For this study, 17 samples have voluntarily participated, and they have been arranged in pairs to compare these individuals. Inquiries about different resonating ride segments and non-resonating ride segments have been made for the samples to answer. The objective of this action is to ensure that constant values of frequency weighted R. M. S. vibration remain at the same level. As such, the current experimental technique employed would technically require a range of modifications and review at some point – mainly concerning the seat’s structural dynamics, where the designs and positions of the experimental technique’s structure is of particular concern. The main target of this research would be to contribute significantly to the domain of ride comfort and body vibration, in which researchers would produce quantitative outputs that can be referred to and utilized in the future as an improvisation for the existing test standards.